PERAN LAYANAN KONSELING INDIVIDU DENGAN PENDEKATAN SOLUTION FOCUSED BRIEF COUNSELING DALAM MENANGANI PERILAKU CHRONICALLY ONLINE PADA SISWA KELAS 11 SMA NEGERI COLOMADU TAHUN AJARAN 2024/2025 - Samuel Barukh Manindra Putra; Jawandi, Ahmad; Adi Putro, Eko (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The purpose of this study was to determine the role of individual counseling services with a Solution Focused Brief Counseling (SFBC) approach in addressing chronically online behavior among an eleventh-grade student at Senior High School Colomadu during the 2024/2025 academic year. This research was conducted at Senior High School Colomadu. The subject in this study was one high school student. This research is a Guidance and Counseling Action Research (PTBK) which was carried out in 2 cycles. Each cycle consists of 4 stages, namely, planning, action, observation, and reflection. Data collection techniques used in this study were observation, interviews and documentation. In the first cycle of action research, the results obtained chronically online behavior decreased, but there were still several indicators that had not been resolved properly with a percentage of 59,25%. Next, these results were evaluated and then the researcher provided action in the second cycle. In the second cycle of action research, the results showed a decrease in chronically online behavior by 33,33%, reaching the target set by the researcher. It can be concluded that individual counseling services using the Solution Focused Brief Counseling (SFBC) approach can address chronically online behavior in eleventh-grade students Senior High School Colomadu during the 2024/2025 academic year.